Metal enhanced fluorescence of thiacyanine dye in layered polymer films - Pereverzev, N.V.; Borovoy, I.A.; Sedyh, O.O.; Yefimova, S.L.; Sorokin, A.V. (Functional Materials, 2014)
The metal enhanced fluorescence of thiacyanine dye monomers in polymer films has been studied. To control the distance between dye molecules and silver nanoparticles a polymer spacer has been used. The spacer thickness has been varied using a layer-by-layer assembly method of polyelectrolytes. The best 4.5 times fluorescence enhancement has been observed for the 20 nm thick polymer spacer. The result has been confirmed both by steady-state and time-resolved fluorescence spectroscopies.